Feasibility and Preliminary Effects of a Community‐Based Sutra Chanting Program on Mental Well‐Being and Respiratory and Swallowing Functions in Older Adults: A Pilot Study. - Edahiro, Ayako; Ura, Chiaki; Motohashi, Yoshiko; Kaneko, Mayumi; Ando‐Ohmura, Chiaki; Shirobe, Maki; Hayakawa, Misato; Shoji, Ryosho; Kaneko, Reisai; Ogawa, Yukan; Takase, Akinori; Okamura, Tsuyoshi (Geriatrics & Gerontology International, 2026)
Aim: To explore the feasibility and preliminary effects of a community‐based health program incorporating sutra chanting on mental well‐being and respiratory and swallowing‐related functions in community‐dwelling older adults. Methods: This pilot study employed a single‐group pre–post design. Community‐dwelling older adults participated in a 7‐week sutra chanting program held weekly at Buddhist temples in Tokyo. Mental well‐being was assessed using the WHO‐5 Well‐being Index. Respiratory and swallowing‐related functions were evaluated using forced expiratory volume in 1 s (FEV1.0), maximum phonation time (MPT), and hyoid displacement during swallowing (ΔHD). Changes from pre‐ to post‐intervention were analyzed using mixed models for repeated measures. Results: A total of 44 participants (mean age 70.3 ± 9.1 years) completed the program without adverse events. Mixed‐model analyses revealed significant improvements in WHO‐5 well‐being scores, MPT, FEV1.0, and ΔHD following the intervention. No significant changes were observed in tongue pressure or repetitive saliva swallowing test scores. Qualitative feedback indicated perceived calmness, emotional comfort, and motivation to continue chanting. Conclusions: Participation in a community‐based sutra chanting program was feasible and safe and was associated with significant pre–post changes in mental well‐being and selected respiratory and swallowing‐related measures in older adults. Traditional cultural practices such as sutra chanting may represent promising complementary resources for community‐based health promotion in aging societies. Further controlled studies are warranted to confirm these preliminary findings.